Optimization of Tensile Strength of Friction Welded AISI 1040 and AISI 304L Steels According to Statistics Analysis (ANOVA) - Kirik, Ihsan; Ozdemir, Niyazi; Firat, Emrah Hanifi; Caligulu, Ugur (Carl Hanser Verlag, 2013)
Materials difficult to weld by fusion welding processes can be successfully welded by friction welding. The strength of the friction welded joints is extremely affected by process parameters (rotation speed, friction time, friction pressure, forging time, and forging pressure). In this study, statistical values of tensile strength were investigated in terms of rotation speed, friction time, and friction pressure on the strength behaviours of friction welded AISI 1040 and AISI 304L alloys. Then, the tensile test results were analyzed by analysis of variance (ANOVA) with a confidence level of 95 % to find out whether a statistically significant difference occurs. As a result of this study, the maximum tensile strength is very close, which that of AISI 1040 parent metal of 637 MPa to could be obtained for the joints fabricated under the welding conditions of rotation speed of 1700 rpm, friction pressure of 50 MPa, forging pressure of 100 MPa, friction time of 4 s, and forging time of 2 s. Rotation speed, friction time, and friction pressure on the friction welding of AISI 1040 and AISI 304L alloys were statistically significant regarding tensile strength test values.
Keywords: Low-Alloy Steel; Stainless-Steel; Mechanical-Properties; Rotational Speed; Aisi-4340 Steel; Welding Process; Carbon-Steel; Joints; Aisi-304L